2009
DOI: 10.1111/j.1365-2125.2009.03443.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and nature of drug–drug interactions in a Dutch university hospital

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Drug–drug interactions (DDIs) may lead to often preventable adverse drug events and health damage. • In Dutch community pharmacies approximately 6% of all prescriptions generate a DDI alert. • Hospitalized patients may be especially at risk, as they are more severely ill and multiple medications may be prescribed simultaneously; however, only limited data are available on the frequency and nature of DDIs during hospitalization. WHAT THIS STUDY ADDS • In a Dutch uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 24 publications
3
98
2
5
Order By: Relevance
“…The results of our study show that the prevalence of pDDIs in the psychiatric ward (64.8%) was higher compared to other hospitalized patients (49.7 % [3] and 27.8 % [2]) or patients of other wards such as internal medicine wards (51 % [4] and 60 % [13] ) and oncology wards (63 % [5]). In our study, prevalence of pDDIs of major severity (27.2 %) was also higher compared to other studies.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The results of our study show that the prevalence of pDDIs in the psychiatric ward (64.8%) was higher compared to other hospitalized patients (49.7 % [3] and 27.8 % [2]) or patients of other wards such as internal medicine wards (51 % [4] and 60 % [13] ) and oncology wards (63 % [5]). In our study, prevalence of pDDIs of major severity (27.2 %) was also higher compared to other studies.…”
Section: Discussionmentioning
confidence: 70%
“…The issue of DDIs needs more attention in the case of hospitalized patients due to severity of disease, polypharmacy, co-morbid conditions, chronic diseases, complex therapeutic regime, and frequent modification in therapy [2]. Prevalence of potential DDIs (pDDIs) in hospital settings has been estimated in some recent studies to be in the range of 27.8 to 51.4 % [2][3][4]. Old age, taking increased number of medications, long hospital stay, gender and comorbid conditions have been reported as common risk factors for DDIs [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In our study this factor only accounted for 5% of the preventable ADRs. Most drug-drug interactions can be handled with dose adjustment or monitoring of laboratory values [24]. Also there is an increasing use of electronic medical records with automatic systems to detect some of these drug interactions that could potentially lead to an ADR.…”
Section: Discussionmentioning
confidence: 99%
“…Experience from participation in ward rounds and previous studies30 suggest that potential DDI are frequently underestimated. Recently published large studies from university and primary care hospitals reported DDIs (ranging from contraindicated to no clinical relevance) in 27%–28% of all inpatients 29 31…”
Section: Discussionmentioning
confidence: 99%